Efficacy of low doses of terlipressin to prevent intra-operative blood loss in obstetrics - Yu. S. Аleksandrovich; A. V. Rostovtsev; E. S. Kononova; K. V. Pshenisnov; T. I. Аkimenko (Вестник анестезиологии и реаниматологии, 2020)
The use of modern blood-saving technologies is one of the effective methods of preventing intra-operative bleeding in obstetric practice, however, the effect of local use of terlipressin to reduce blood loss is not sufficiently investigated.The objective: to assess the efficacy of local preventive use of low doses of terlipressin to reduce of intra-operative blood loss in the cesarean section.Subjects and methods. 105 women who underwent the cesarean section under spinal anesthesia were examined. They were divided into 3 groups depending on the administered dose of terlipressin: Group 1 (n = 35) ‒ 0.2 mg, Group II (n = 35) ‒ 0.4 mg, Group III (n = 35) ‒ control one. The swab-weighing method was used to assess blood loss.Results. In Group I, the blood loss made 6.9% of the total blood volume, in Group II ‒ 7.7%, and in Group III ‒ 13.3%. The frequency of hemotransfusion in Group I was ‒ 0%, in II ‒ 2.9%, in III ‒ 14.3%. No complications and side effects associated with terlipressin use were observed.Conclusion. The use of low doses of terlipressin for prevention purposes has a sufficiently pronounced clinical effect and is not accompanied by any complications.